Cultural Da'wah and Islamic Acculturation in the Architecture of the Cheng Ho Sriwijaya Mosque in Palembang - Putrajaya, Nurhan; Hasanah, Uswatun; Syawaludin, Mohammad; Ibrahim, Duski (MUHARRIK: Jurnal Dakwah dan Sosial, 2026)
Research on da’wah has generally focused on sermons, communication strategies, and religious institutions, while the role of architecture as a medium of cultural da’wah has received relatively little conceptual and theoretical attention. This study aims to analyze how the architecture of the Cheng Ho Sriwijaya Mosque in Palembang functions as a symbolic medium in representing the acculturation of Islam within a multicultural society. This study is a qualitative research employing an experimental archaeology approach enriched by multidisciplinary perspectives, particularly studies in da’wah, architecture, and the semiotics of space. Data were collected through observations of architectural elements, analysis of documentation, and interviews with administrators and congregants. The results indicate that the mosque’s design represents da’wah communication through the integration of Chinese aesthetics, Malay cultural symbols, and Islamic spiritual values, manifested in the form of pagodas, color symbolism, and decorative motifs. These findings not only affirm the symbolic function of architecture as discussed in previous literature but also demonstrate that physical space operates as a non-verbal communication system that directly shapes the congregants’ religious experience. Theoretically, this study proposes the concept of cultural-architectural da’wah, a framework that positions architecture as an active medium in transmitting Islamic values through visual symbols and spatial experiences. Unlike cultural da’wah approaches that focus on social practices, this concept emphasizes the material-spatial dimension as an agent of religious communication. This study is expected to advance the development of da’wah studies, particularly in the field of culture-based da’wah communication, and to enrich the body of knowledge in Islamic architecture and cultural studies through the integration of spatial semiotics perspectives. These findings expand our understanding of Islamic acculturation by positioning architectural space as an active and communicative medium of da’wah; as a single case study, these findings are contextual in nature. Future research should test this framework comparatively across cultures to strengthen its conceptual validity.